2018
DOI: 10.1186/s12886-018-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of capillary dropout in the superficial retinal capillary plexus by optical coherence tomography angiography in the early stage of diabetic retinopathy

Abstract: BackgroundTo assess capillary dropout in the superficial retinal capillary plexus (SCP) by optical coherence tomography angiography (OCTA) in the early stage of diabetic retinopathy (DR).MethodsThis study was a cross-sectional observational study. Patients that underwent OCTA examinations in our hospital between November 2015 and May 2016 were included in the study. The subjects were divided into two groups: A) normal controls (41 eyes of 41 subjects) and B) the DR patients (49 eyes of 49 patients with mild no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…In the early stage of nonproliferative DR, capillary dropout was also identified in the superficial capillary plexus. 9 A decreased vessel density has also been reported in both the superficial and deep capillary plexuses in type 2 diabetes mellitus without DR. 28 In contrast to the 6 × 6-mm 2 scans used in our study, previous studies cited herein have used the central 3 × 3-mm 2 scan for their analysis. Interstudy differences in the retinal segmentation presets among OCT-A imaging systems and the lack of correction for the differences in segmentation boundaries can cause significant errors in OCT-A measurements.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the early stage of nonproliferative DR, capillary dropout was also identified in the superficial capillary plexus. 9 A decreased vessel density has also been reported in both the superficial and deep capillary plexuses in type 2 diabetes mellitus without DR. 28 In contrast to the 6 × 6-mm 2 scans used in our study, previous studies cited herein have used the central 3 × 3-mm 2 scan for their analysis. Interstudy differences in the retinal segmentation presets among OCT-A imaging systems and the lack of correction for the differences in segmentation boundaries can cause significant errors in OCT-A measurements.…”
Section: Discussionmentioning
confidence: 87%
“…Most reported a decrease in perifoveal perfusion parameters in the deep retinal layer, 6,7 or in the superficial layer. 8,9 However, Goudot et al 10 found no significant differences, and Rosen et al 11 described greater capillary perfusion in diabetics with no DR compared with controls.…”
mentioning
confidence: 99%
“…The high resolution details have been proved to be consistent to those in the anatomic and histological images [29,35,57,58], as an example shown in Figure 4, which makes OCT to be called "optical biopsy". Actually, compared with widely used clinic tomography modalities, the key advantage of OCT is its micrometer resolution which enables the detection of tiny pathological changes and validated the comparable performance of OCT in clinic with some gold diagnosing standards [14,59,60], making OCT a potential clinic alternative in condition of contraindication, tissue removal impossible, avoiding tissue destruction and so on. Take ultrasonic tomography which has similar theory and ability to be used in endoscopy with OCT as example, Mueller-Lisse [61] compared the endoluminal ultrasonography and OCT images of porcine upper urinary tract, and demonstrated the better performance of OCT in distinguishing between urothelium, lamina propria, and muscle layer.…”
Section: Advantage and Limitationmentioning
confidence: 99%
“…The vision-affecting-diseases and therapeutic progress change the characters of eye layers [10][11][12][13][14]. The most commonly used markers in ophthalmological OCT diagnosing are retinal thickness, retinal layer structure and choroidal thickness.…”
Section: Oct In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation